2022
DOI: 10.1101/2022.05.16.22275166
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolomic Risk Predictors of Diabetic Foot Complications: a longitudinal observational study in Type 1 Diabetes

Abstract: Diabetic foot complications is a collective term used for the ailments of the foot that individuals with diabetes incur. The different entities of the term diabetic foot complications are closely linked to each other and several of the other complications of diabetes. Despite implementation of national and international preventive guidelines, diabetic foot complications are still a growing challenge to the individual and society in general. This highlights the need for new strategies in the treatment and preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Through these studies, we have identified hydroxybutyrate isomers, ribose derivatives, and branched-chain amino acids that were associated with presence and development or progression of DR,8 kidney disease,5 and cardiovascular disease 10. Similar results were also identified in relation to cardiac autonomic neuropathy 4 11. Distal symmetric polyneuropathy (DSPN) remains to be investigated using similar methods.…”
Section: Introductionmentioning
confidence: 78%
“…Through these studies, we have identified hydroxybutyrate isomers, ribose derivatives, and branched-chain amino acids that were associated with presence and development or progression of DR,8 kidney disease,5 and cardiovascular disease 10. Similar results were also identified in relation to cardiac autonomic neuropathy 4 11. Distal symmetric polyneuropathy (DSPN) remains to be investigated using similar methods.…”
Section: Introductionmentioning
confidence: 78%